Pregnancies in older women living with HIV in the UK and Ireland. Issue 7 (16th November 2016) - Townsend, CL; de Ruiter, A; Peters, H; Nelson‐Piercy, C; Tookey, P; Thorne, C
Abstract : Objectives: The aim of the study was to compare maternal characteristics and pregnancy outcomes in women aged < 40 years and ≥ 40 years in a large unselected population of HIV‐positive women delivering in the UK and Ireland between 2000 and 2014. Methods: Comprehensive population‐based surveillance data on all HIV‐positive pregnant women and their children seen for care in the UK and Ireland are collected through the National Study of HIV in Pregnancy and Childhood. All singleton and multiple pregnancies reported by the end of June 2015 resulting in live birth or stillbirth to women diagnosed with HIV infection before delivery and delivering in 2000−2014 were included. Logistic regression models were fitted in analyses examining the association between older maternal age and specific outcomes (preterm delivery and stillbirth). Results: Among 15 501 pregnancies in HIV‐positive women, the proportion in older women (≥ 40 years) increased from 2.1% (73 of 3419) in 2000−2004 to 8.9% (510 of 5748) in 2010−2014 ( P < 0.001). Compared with pregnancies in younger women, those in older women were more likely to result in multiple birth (3.0 vs . 1.9% in younger women; P = 0.03), stillbirth (adjusted odds ratio 2.39; P = 0.004) or an infant with a chromosomal abnormality (1.6 vs . 0.2%, respectively; P < 0.001). However, there was no increased risk of preterm delivery, low birth weight or mother‐to‐child HIV transmission among older mothers. Conclusions: There has been a significant increase over time in the proportion of deliveries to women living with HIV aged ≥ 40 years, which has implications for pregnancy management, given their increased risk of multiple births, stillbirth and chromosomal anomalies, as also apparent in the general population.